2016
DOI: 10.1080/03067319.2016.1180380
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the number of phthalates monitored in house dust

Abstract: Phthalates have been used as plasticisers for several decades in various industry and consumer products. A method was developed for the determination of 13 not commonly monitored phthalates in household dust. The method was based on solvent extraction using sonication, sample clean-up by solid phase extraction (SPE), and analysis using isotope dilution gas chromatography-tandem mass spectrometry (GC/MS/MS). The method was applied to the analysis of dust samples collected using two vacuum sampling techniques fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, there was no significant difference between the geomean values (Student's ttest p = 0.3886) of the HD and FD datasets. These observations are consistent with previous studies of synthetic organics in dust (e.g., musks, phthalates, organophosphate esters, bisphenol A,) which reported significant correlations for most compounds determined in matched HD and FD samples [49][50][51][52]. Similarly, Rasmussen et al [53] reported significant positive correlations (p < 0.001) between concentrations measured in matched HD and FD samples for 17 metals, with moderate to strong Spearman rho values (0.40-0.76).…”
Section: Comparison Of Sampling Methods (Fd Vs Hd)supporting
confidence: 92%
“…Furthermore, there was no significant difference between the geomean values (Student's ttest p = 0.3886) of the HD and FD datasets. These observations are consistent with previous studies of synthetic organics in dust (e.g., musks, phthalates, organophosphate esters, bisphenol A,) which reported significant correlations for most compounds determined in matched HD and FD samples [49][50][51][52]. Similarly, Rasmussen et al [53] reported significant positive correlations (p < 0.001) between concentrations measured in matched HD and FD samples for 17 metals, with moderate to strong Spearman rho values (0.40-0.76).…”
Section: Comparison Of Sampling Methods (Fd Vs Hd)supporting
confidence: 92%
“…17 The HD>FD trend observed for REEs is the reverse of trends observed for many organic compounds in the CHDS (eg, parabens, synthetic musks, alklyphenols, phthalates, and organophosphate esters). [20][21][22][23][24][25][26] For those organic compounds which displayed a significant difference in FD compared to HD samples, the majority showed FD>HD, probably caused by losses due to volatilization and/ or decomposition during the longer residence time in the household vacuum system. 26…”
Section: Nationally Representative Ree Concentrations In Fd and Hdmentioning
confidence: 99%
“…4,12 The 1025 participating homes in the Canadian House Dust Study (CHDS) were randomly sampled from 13 cities, and previous CHDS papers reported national baseline data for arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), lead (Pb), nickel (Ni), zinc (Zn), and selenium (Se), [17][18][19] plus many organic compounds including flame retardants, phthalates, BPA, parabens, and musks. [20][21][22][23][24][25][26] Technicians followed a vacuum sampling protocol designed to collect a consistent composite (whole-house) sample of readily accessible "fresh dust" of known age, from dry floor surfaces of known dimensions, which yielded measurements of both elemental concentration and elemental loading.…”
mentioning
confidence: 99%
“…Data summaries for all of the substances included in this paper are provided in the Supplementary Information (SI-6 to SI-16) , and details of the analytical methods were published previously. Analytical approaches were developed or optimized, in Health Canada laboratories, to provide quantitative determinations of the synthetic organic compounds [ 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 54 ]. Total element concentrations were determined using Inductively Coupled Plasma Mass Spectrometry (ICP–MS), Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), Instrumental Neutron Activation Analysis (INAA), or (in the case of mercury) direct solid sample analysis using atomic absorption spectrometry [ 17 , 22 , 47 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Composite (whole-house) vacuum dust samples were collected from 13 cities during the winter season of 2007 to 2010 (incl.) and analysed quantitatively for organic and inorganic contaminants [ 17 , 22 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. This study uses Spearman rank analysis to identify relationships between house characteristics and 59 elements (metals and metalloids), and >200 synthetic organics, including phthalates; bisphenol A (BPA) and BPA analogues; organophosphate esters (OPEs); halogenated flame retardants including polybrominated diphenyl ethers (BDEs); octylphenol and nonylphenol ethoxylates; aryl and alkyl-aryl phosphates; bactericides (parabens); pesticides (e.g., permethrin, organochlorines); and synthetic musks.…”
Section: Introductionmentioning
confidence: 99%